Advanced-Glycation End-Products Induce Podocyte Injury and Contribute to Proteinuria - Nishad, Rajkishor; Tahaseen, Vazeeha; Kavvuri, Rajesh; Motrapu, Manga; Singh, Ashish K; Peddi, Kiranmayi; Pasupulati, Anil K (Frontiers in Medicine, 2021)
The prevalence of diabetes reaches epidemic proportions. Diabetes is the leading cause of end-stage kidney disease (ESKD) since 30-40% of diabetic patients develop diabetic nephropathy. Albuminuria and glomerular filtration rate used to assess kidney function are considered surrogate outcomes of chronic kidney disease. The search for a biomarker that predicts progression to diabetic kidney disease is intense. We analyzed the association of serum advanced glycation end-products (AGEs) index (AGI) with impaired kidney function in poorly controlled type II diabetic patients. We observed an association between AGI and impaired kidney function in microalbuminuria patients with hyperglycemia. A significant association between AGEs, particularly carboxymethyl lysine (CML), and impaired kidney function were observed. Administration of AGEs to mice showed heavy proteinuria and glomerular abnormalities. Reduced podocyte number in mice administered with AGEs could be attributed to the epithelial-mesenchymal transition of podocytes. Our study suggests CML could be independently related to the podocyte injury and the risk of DN progression to ESKD in patients with microalbuminuria. AGEs in general or CML could be considered a prognostic marker to assess diabetic kidney disease.